Janeway Lesions in Systemic Lupus Erythematosus - Anam, Ahmad Mursel; Shumy, Farzana; Shareef, Adnan; Rabbani, Raihan (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Abstract not available J Bangladesh Coll Phys Surg 2016; 34(1): 48-49